Metagenomics of microbial diversity in both active and closed landfills and their tolerance towards selected heavy metals / Mohamad Yusof Zainun - Mohamad Yusof , Zainun (2019)
The municipal landfill is an example of human-made environment that contain high level of heavy metals contamination and harbors a complex diversity of microorganisms. To evaluate the landfill complexity, this study aims to assess the structures of bacterial communities in active and closed landfills with culture independent metagenomics approaches. At the same time, the potential of indigenous landfill bacteria to treat heavy metals and their succession in bioaugmentation process were analysed. Several points of soil samples were collected from 0 to 20 cm depth and were subjected to physicochemical test. The bacterial enumeration was examined while the microbial soil DNA was extracted prior to sequence the 16S rRNA gene for bioinformatics analyses. As a result, the higher bacterial operational taxonomic units (OTUs) sequenced was recorded in closed landfills compared to active landfill i.e. 6625 and 4552 OTUs respectively. The data from both landfills showed that the predominant phyla belonged to Proteobacteria (55.7 %). Bacteroidetes was the second highest phylum followed by Firmicutes for the active landfill. While the phyla for communities in closed landfill were dominated by phyla from Acidobacteria and Actinobacteria. These composition of bacterial communities shows some variances between the bacterial communities found in active and closed landfills. On the other hand, twenty nine heavy metal resistant bacteria were isolated from both landfills displayed different degree of metal ions tolerance. The STB7 strain with identification as Delftia tsuruhatensis shown the most potential isolate toward the test. The result in preliminary tests of the isolated microbes suggests their suitability for enhanced bioremediation of heavy metal polluted environment. Furthermore, the succession of inoculated bacteria that potentially to treat heavy metal in landfill soil were assessed via denaturing gradient gel electrophoresis (DGGE) approach. The result shown the inoculated bacteria treatment of bacteria into soil sample did survive at the beginning of treatment before gradually disappear when the time passes, especially when reaching 100 days incubation.